2003
DOI: 10.1103/physrevlett.90.127901
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Coupling of Superconducting Qubits

Abstract: We study an LC circuit implemented using a current-biased Josephson junction (CBJJ) as a tunable coupler for superconducting qubits. By modulating the bias current, the junction can be tuned in and out of resonance and entangled with the qubits coupled to it. One can thus implement two-qubit operations by mediating entanglement. We consider the examples of CBJJ and charge-phase qubits. A simple recoupling scheme leads to a generalization to arbitrary qubit designs.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
165
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(169 citation statements)
references
References 24 publications
(46 reference statements)
1
165
0
3
Order By: Relevance
“…[12][13][14] With regard to using superconducting systems in quantum technologies, it has been shown that Josephson weak link circuits, and in particular SQUID rings in the quantum regime, are highly nonperturbative in nature and can generate very strong nonlinear interactions with classical circuit environments. [15][16][17][18] In this paper we provided a demonstration that this nonperturbative ͑nonlinear͒ behavior is crucial to the understanding of the interaction of SQUID rings with circuit environments. In this work we first consider the adiabatic ͑ground state͒ interaction of a quantum regime SQUID ring inductively coupled to a classical parallel resonance LC ͑tank͒ circuit.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] With regard to using superconducting systems in quantum technologies, it has been shown that Josephson weak link circuits, and in particular SQUID rings in the quantum regime, are highly nonperturbative in nature and can generate very strong nonlinear interactions with classical circuit environments. [15][16][17][18] In this paper we provided a demonstration that this nonperturbative ͑nonlinear͒ behavior is crucial to the understanding of the interaction of SQUID rings with circuit environments. In this work we first consider the adiabatic ͑ground state͒ interaction of a quantum regime SQUID ring inductively coupled to a classical parallel resonance LC ͑tank͒ circuit.…”
Section: Introductionmentioning
confidence: 99%
“…Let δ = B z − ω be the detuning. If we let the PCB and the (initially un-excited) LC resonator interact right in resonance, i.e., |δ − 2γ| ≪ g ≪ ω or |δ + 2γ| ≪ g ≪ ω [23], state transfer occurs between the PCB and the LC resonator [13,14]. This is not allowed in our scheme, since it will drive the PCB out of the DFS.…”
mentioning
confidence: 99%
“…Schemes allowing to compute with invariable couplings were also studied [11,12]. Others have recently discussed to use an LC circuit to actively mediate the interaction between superconducting qubits [13,14].The requirement to reduce decoherence and the desire for the easiest manipulation apply to all QIP implementations. Unfortunately, it is not always easy to accomplish both -actually the goals are often contradictory -since reducing decoherence may require extra complication in the manipulation.…”
mentioning
confidence: 99%
See 2 more Smart Citations